2010
DOI: 10.2528/pierl10061301
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth Behaviors of Primary Phase in Al-Cu Hypereutectic Alloy in High Magnetic Fields

Abstract: Abstract-The nucleation and growth of primary Al 2 Cu phase in the Al-34.3wt%Cu hypereutectic alloy without and with magnetic fields have been investigated by differential thermal analysis (DTA). The DTA curves indicated that the nucleation temperature of primary phase was significantly reduced in a magnetic field. The X-ray diffraction (XRD) patterns confirmed that the c-axes of primary Al 2 Cu crystals oriented along the direction parallel to a magnetic field. The microstructures showed that primary crystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…6) On the other hand, solidification under a magnetic field has also been reported to directly yield crystal aligned structures in various alloys. [20][21][22][23][24][25][26][27][28][29][30][31][32] Iwai and Usui 20) showed that the c-axis of the Bi-rich primary phase in Bi-10 mass % Sn alloys can be aligned by simply applying a 8 T magnetic field during solidification. Legrand et al 21) succeeded in forming highly c-axis aligned Sm-Co alloys by applying a 2.5 T magnetic field during rapid solidification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) On the other hand, solidification under a magnetic field has also been reported to directly yield crystal aligned structures in various alloys. [20][21][22][23][24][25][26][27][28][29][30][31][32] Iwai and Usui 20) showed that the c-axis of the Bi-rich primary phase in Bi-10 mass % Sn alloys can be aligned by simply applying a 8 T magnetic field during solidification. Legrand et al 21) succeeded in forming highly c-axis aligned Sm-Co alloys by applying a 2.5 T magnetic field during rapid solidification.…”
Section: Introductionmentioning
confidence: 99%
“…The c-axis alignment of primary MnBi in the Bi-Mn system with various Mn contents solidified under a magnetic field has been studied by several groups. [22][23][24][25][26] Li et al 27) solidified a Al-34.3 mass % Cu alloy under 2-12 T magnetic fields and observed a c-axis alignment of Al 2 Cu crystals increasing proportionally to magnetic field intensity. Usui et al 28) reported that crystal alignment of Sn-Pb alloy is possible by directly applying a magnetic field of 7.5 T during solidification when the primary Sn-rich phase was dispersed by electromagnetic oscillation.…”
Section: Introductionmentioning
confidence: 99%